The treatment of canine mast cell tumours with electrochemotherapy with or without surgical excision. (22nd March 2016) - Lowe, R.; Gavazza, A.; Impellizeri, J. A.; Soden, D. M.; Lubas, G.
Abstract: To describe the results of electrochemotherapy (ECT) in dogs with mast cell tumours (MCTs) either as first line therapy or as an adjuvant to surgery. The treatment combines administration of low dose chemotherapeutic drugs with the application of microsecond electric pulses, which cause the temporary permeabilization and increased porosity of the tumour cell membranes. The design of this study is a retrospective case series. A total of 51 dogs with MCTs were included and classified according to ECT procedure into 4 groups (ECT only, 15 cases, intra‐surgery ECT, 11, ECT Adjuvant to surgery, 14, Surgery followed by ECT, 11). The four groups (staged with location, size and grade) were evaluated to assess complete or partial remission, disease free interval, overall survival time and local toxicity. In this case series, Boxers, mixed breed and Labrador Retrievers, male dogs, between 4 and 9 years old were more represented. MCTs were predominantly grade 2 (Patnaik) and T stage 0–1, I‐1 (World Health Organization). Treated lesions were most commonly identified on the hindlimb and head where curative surgery would involve cosmetic or functional compromise. The intra‐surgery group of dogs showed the best disease free interval with Kaplan–Meyer analysis. Local toxicity induced by ECT ranged mostly from 1 to 4 in a 5‐point arbitrary scale with 0 – no toxicity to 5 – highest toxicity. In this study, ECT can be applied successfully as an exclusive therapy in smaller MCTs as an alternative to surgery. ECT can be combined with surgery either intra‐operatively or post operatively for larger lesions without significant toxicity.